2011
DOI: 10.1002/meet.2011.14504801304
|View full text |Cite
|
Sign up to set email alerts
|

Self extension and the desire to preserve digital possessions

Abstract: Developed from psychology and sociology, the concept of self extension means that an individuals' concept of his or her own self can extend outside the body (Belk, 1988). While studies in the context of consumer behavior have explored many applications of self extension to material objects, self extension to digital objects has yet to be explored. Further, self extension to possessions can influence behavior and may therefore influence maintaining behavior, or the actions associated with saving or personal inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 6 publications
(5 reference statements)
0
11
0
1
Order By: Relevance
“…Cushing () conducted an exploratory study to determine how self‐extension to digital possessions could influence preservation practices. The results indicated that some participants could perceive their self to be extended to their digital possessions, to varying degrees.…”
Section: Literature Review: Individual–digital Item Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Cushing () conducted an exploratory study to determine how self‐extension to digital possessions could influence preservation practices. The results indicated that some participants could perceive their self to be extended to their digital possessions, to varying degrees.…”
Section: Literature Review: Individual–digital Item Relationshipmentioning
confidence: 99%
“…Cox concluded that professional archivists should address the issues presented by personal archival collections, specifically by providing assistance to individuals to maintain their personal archival collections. Cushing (2011) conducted an exploratory study to determine how self-extension to digital possessions could influence preservation practices. The results indicated that some participants could perceive their self to be extended to their digital possessions, to varying degrees.…”
Section: Literature Review: Individual-digital Item Relationshipmentioning
confidence: 99%
“…Recently, there has been much speculation in the media concerning the existence of and potential problems relating to digital hoarding. The existence of digital hoarding is not surprising given that our lives are becoming increasingly digital (Gulotta et al 2013) and that contemporary presentations of the self extend to digital possessions (Cushing 2011(Cushing , 2013). Yet relatively little research describes the accumulation of digital possessions and addresses the potentially unique issues and problems that digital hoarding might create.…”
Section: Introductionmentioning
confidence: 99%
“…Esse contato entre grupos e outros usuários é gerado pela facilidade de agregação por meio da comunicação em rede. Deste modo, a construção de grupos por afinidades (CUSHING, 2011;RECUERO, 2013) direciona o usuário do Facebook a demonstrar um comportamento solidário às suas causas simpatizantes, remetendo a uma conduta ativista.…”
Section: Discussionunclassified